Overview on the species composition of the landsnails fauna of Vietnam - Thanh, Dang Ngoc (Academia Journal of Biology, 2014)
In Vietnam, researsch on the landsnails fauna has begun since the middle of the XIX Century, with the first publication of Souleyet (1841) on the landsnails of the Indochina Region, including some new species, described from central part of Vietnam (Tourane). In the following period, during 60’s years, other important study results on the landsnails fauna of the southern part of Vietnam (Annam, Cochinchine) has been published: Crosse et Fischer (1863, 1854, 1869); Mabille et Le Mesle (1866); Crosse (1867, 1868). Publications on the landsnails species of the northern part of Vietnam occured later, with many very known research works of different authors: Morlet (1855, 1891, 1892); Dautzenberg et Hamonville (1897): Dautzenberg (1893); Bavay et Dautzenberg (1891, 1900, 1901, 1903); Fischer (1848); Mollendorff (1901); Dautzenberg et Fischer (1905). During the war time in Vietnam until 1975, research on the landsnails were almost interrupted, except a few works of Saurin (1955, 1960); Jaeckel (1950); Varga (1963). It continued only after the war, with some recent publications realized in northern part of Vietnam (Vermeulen et Maassen, 2003). Based on the aboved mentioned research results on the landsnails fauna of Vietnam until now, some preliminary remarks could be noted. 1. The species composition of the landsnails fauna of Vietnam, although far to be considered as full, is rather rich and diverse. Until now, totally 776 species has been recorded, essentially from mountain regions of the northern and southern parts of the country. 2. Landsnails fauna of Vietnam is rich of Prosobranchia species, among them, the genera Cyclophorus, (30 species), Alycaeus (11), Pupina (15) are the most high species number groups, living in limestone caves of high humidity of mountain region. 3. The species composition of landsnails of Vietnam, especially of the northern part, is clearly different in comparison with the fauna of the southern part of the indochinese region (Laos, Cambodge, Thailand). 4. Because of the great change in the classification of landsnails in malacology at present times in comparison with the past, it needs a total revision on the taxonomy of published landsnails species composition of Vietnam.